Krüppel-like factors: Three fingers in control - Swamynathan Shivalingappa K (Human Genomics, 2010)
Abstract Krüppel-like factors (KLFs), members of the zinc-finger family of transcription factors capable of binding GC-rich sequences, have emerged as critical regulators of important functions all over the body. They are characterised by a highly conserved C-terminal DNA-binding motif containing three C2H2 zinc-finger domains, with variable N-terminal regulatory domains. Currently, there are 17 KLFs annotated in the human genome. In spite of their structural similarity to one another, the genes encoding different KLFs are scattered all over the genome. By virtue of their ability to activate and/or repress the expression of a large number of genes, KLFs regulate a diverse array of developmental events and cellular processes, such as erythropoiesis, cardiac remodelling, adipogenesis, maintenance of stem cells, epithelial barrier formation, control of cell proliferation and neoplasia, flow-mediated endothelial gene expression, skeletal and smooth muscle development, gluconeogenesis, monocyte activation, intestinal and conjunctival goblet cell development, retinal neuronal regeneration and neonatal lung development. Characteristic features, nomenclature, evolution and functional diversities of the human KLFs are reviewed here.